Criminalization of Unregistered Polygamy under the 2026 Criminal Code: A Maqāṣid al-Sharīʿah Analysis of the Protection of Women’s Rights - Apriani Asnaye (UIN Jurai Siwo Lampung, 2026)
The criminalization of unregistered polygamy under Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP), which will take effect in 2026, reflects a shift in Indonesian family law policy from an administrative approach to a criminal law approach. Polygamous marriages conducted without the consent of the wife and court authorization often result in harm to women, particularly regarding maintenance rights, legal certainty of marriage, and access to justice. This study aims to analyze the criminalization of unregistered polygamy in the KUHP and examine it from the perspective of maqāṣid al-syarī‘ah concerning the protection of women's rights. This research employs a normative legal method with statutory and conceptual approaches. The findings show that the criminalization of unregistered polygamy serves as an instrument for protecting women's rights by strengthening legal certainty and the husband's responsibility. From the perspective of maqāṣid al-syarī‘ah, this policy is consistent with the objectives of preserving lineage (hifẓ al-nasl), life (hifẓ al-nafs), and property (hifẓ al-māl), as well as the principle of preventing harm (dar’u al-mafāsid). However, its effectiveness requires legal education and adequate supervision to prevent the emergence of more concealed polygamous practices. This study concludes that the criminalization of unregistered polygamy is a legal measure that aligns with the objectives of public welfare in Islamic law and the protection of women's rights.